ISOLATION AND IDENTIFICATION OF PHYTOPATHOGENIC FUNGI FROM INFECTED PLANT PARTS - Thilagam, R.; Kalaivani, G.; Hemalatha, N. (International Journal of Current Pharmaceutical Research, 2018)
Objective: The present study deals with the isolation and identification of phytopathogenic fungi. The fungal isolates were Alternaria spp (Tomato early blight), Fusarium oxysporum (Fusarium wilt), Fusarium solani (daming off and root rot), Aspergillus flavus (Ear rot) and Collectotricumspp (Anthracnose). Methods: They were isolated from infected plant parts and were identified on the basis of colony morphology andlacto phenol cotton blue (LPCB) stains were used to identifymicroscopic examination of spore structures. Pure cultures of the isolates were sub cultured and transferred onto differential media; potato dextrose agar, malt extract agar, czapek yeast extract agar and czapek dox agar for species identification using macro morphological characteristicsThe morphological characteristics of these fungal elements showed various kinds of spores have been identified up to genus/species level. Results: This study proves rapid and less expensive techniques to validate a primary alarm of contamination. Conclusion: The fivefungus which were isolated from different plant parts were very effective in distruction of the plant and found that the producionwere reduced due to the infection. This rapid and less expensive techniques to validate a primary alarm of contamination.